PEMBELAJARAN DAN PERKEMBANGAN PESERTA DIDIK KELAS 3 SDN 1 BENDO DALAM PERSPEKTIF AKADEMIK DAN SOSIAL - Najwa Pasha Ramadhani; Muhammad Muson; Surayanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the learning conditions, differences in academic ability, obstacles in reading and understanding the material, and the strategies used by teachers to address the learning difficulties of students in Class 3 at SDN 1 Bendo. This study employs a descriptive qualitative approach using observation and interviews. The informant was the homeroom teacher of Class 3 at SDN 1 Bendo, while the research subjects consisted of 23 students. Data were obtained through direct observation and in-depth interviews regarding the cognitive, social, affective, and linguistic aspects of the students. The research findings indicate that the learning process in Class 3 is quite conducive, with most students actively participating in learning activities. However, there is a wide range of academic abilities, with some students able to grasp the material quickly, while others require repetition and special assistance. The learning barriers identified include difficulty reading complex words, low focus and motivation, and students’ reluctance to express the difficulties they are experiencing. Additionally, there are students who tend to daydream, are less active in learning, and struggle to understand the material due to suboptimal reading skills. To address these issues, the teacher implemented various strategies such as reviewing the material, providing regular practice exercises, collaborative learning through peer tutoring, arranging seating arrangements, and providing special support for students facing learning difficulties. The research results indicate that learning success is influenced by students’ abilities, learning motivation, family support, and the teaching strategies implemented by teachers. Therefore, effective collaboration between teachers, students, and parents is essential to optimally support students’ academic and social development. Keywords: elementary school education, learning difficulties, student development, the role of teachers, motivation to learn, family environment. ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan kondisi pembelajaran, perbedaan kemampuan akademik, hambatan membaca dan pemahaman materi, serta strategi guru dalam mengatasi kesulitan belajar peserta didik kelas 3 SDN 1 Bendo. Penelitian menggunakan pendekatan kualitatif deskriptif dengan metode observasi dan wawancara. Informan penelitian adalah wali kelas 3 SDN 1 Bendo yang berjumlah satu orang, sedangkan objek penelitian terdiri atas 23 siswa. Data diperoleh melalui observasi langsung dan wawancara mendalam mengenai aspek kognitif, sosial, afektif, dan bahasa peserta didik. Hasil penelitian menunjukkan bahwa proses pembelajaran di kelas 3 berlangsung cukup kondusif dengan sebagian besar siswa aktif mengikuti kegiatan belajar. Namun, terdapat perbedaan kemampuan akademik yang cukup beragam, di mana sebagian siswa mampu memahami materi dengan cepat, sementara siswa lainnya memerlukan pengulangan dan pendampingan khusus. Hambatan belajar yang ditemukan meliputi kesulitan membaca kata-kata yang kompleks, rendahnya fokus dan motivasi belajar, serta kurangnya keberanian siswa dalam mengungkapkan kesulitan yang dialami. Selain itu, terdapat siswa yang cenderung melamun, kurang aktif dalam pembelajaran, dan mengalami kesulitan memahami materi karena kemampuan membaca yang belum optimal. Untuk mengatasi permasalahan tersebut, guru menerapkan berbagai strategi seperti pengulangan materi, pemberian latihan soal secara rutin, pembelajaran kolaboratif melalui tutor sebaya, pengaturan tempat duduk, serta pendampingan khusus bagi siswa yang mengalami kesulitan belajar. Hasil penelitian menunjukkan bahwa keberhasilan pembelajaran dipengaruhi oleh kemampuan siswa, motivasi belajar, dukungan keluarga, serta strategi pembelajaran yang diterapkan guru. Oleh karena itu, diperlukan kerja sama yang baik antara guru, siswa, dan orang tua untuk mendukung perkembangan akademik maupun sosial peserta didik secara optimal. Kata Kunci: pembelajaran sekolah dasar, kesulitan belajar, perkembangan peserta didik, peran guru, motivasi belajar, lingkungan keluarga